Analyzing Influences on Premarital Behavior Among Adolescents Through Cross-sectional Analysis: Efektivitas Intervensi Kalsium dan Aspirin dalam Pencegahan Preeklampsia - Azizah, Siti Nur; Amelia, Paramitha; Faridah Hanum, Sri Mukhodim; Cholifah, Siti (Academia Open, 2024)
This study examines the factors influencing premarital sexual behavior among high school students at SMAN 1 Wonoayu. Findings reveal significant associations between knowledge, religiosity, peer influence, and technology with premarital sexual behavior. Recommendations include enhancing coordination between healthcare professionals and educational institutions to improve awareness and involving relevant government sectors in addressing this issue. Highlight: <div class="min-h-[20px] text-message flex flex-col items-start whitespace-pre-wrap break-words [.text-message+&]:mt-5 juice:w-full juice:items-end overflow-x-auto gap-3" dir="auto" data-message-author-role="assistant" data-message-id="7e6571d4-be67-45a1-865a-576e727e58b1"> Factors: knowledge, religiosity, peers, technology affect premarital behavior. Cross-sectional study: high school students, analyze influencing factors. Recommendations: enhance coordination between sectors, address premarital behavior effectively. Keyword: premarital behavior, adolescents, influencing factors, knowledge, religiosity.